An Edition of Jonson’s Entertainment at Britain’s Burse and a New Letter by Collier on Massinger in the Athenaeum (1857) - Blaine, Marlin E. (Early Theatre, 2023)
This article identifies two previously uncatalogued items that were published in the Athenaeum in November 1857, each of which is connected to the then-recent acquisition of the Conway Papers by the Public Record Office (now the National Archives). These include a printing of Jonson’s Entertainment at Britain’s Burse and a letter from John Payne Collier that seems to refer to Massinger’s lost play Philenzo and Hippolyto. The former nuances the publication history of a work whose historical and dramatic importance recent scholarship demonstrates, while the latter offers evidence regarding Collier’s claim that a manuscript of Massinger’s play once lay among the Conway Papers.